The political economy of bundling socio-technical innovations to transform agri-food systems - Barrett, Christopher B. (International Food Policy Research Institute, 2023)
Agri-food systems transformation requires accelerated innovations to address multiple economic, environmental and health objectives. No innovation serves everyone’s interests. Political opposition to innovations is therefore inevitable. Promotion of agrifood systems innovations requires overcoming such opposition. One strategy is to bundle multiple technological, socio-cultural, policy, and/or institutional innovations to build political coalitions sufficient to champion bundled innovation that might not suffice to advance one-off innovations. Bundling can translate the potential Pareto improvements of individual innovations into actual Pareto improvements more likely to enjoy political support and advance multiple societal objectives simultaneously. This chapter lays out conceptually why bundling is therefore important for the political economy of innovation to transform agri-food systems. It then illustrates the logic using three cases from Asian agricultural development: China’s Science and Technology Backyards program, a comparison of genetic advances in Green Revolution and golden rice, and the contrasting cases of Bt brinjal in India and Bangladesh.